Unravelling the influence of mixed layer depth on chlorophyll-a dynamics in the Red Sea - Marianthi Pateraki; Dionysios E. Raitsos; George Krokos; Iason Theodorou; Ibrahim Hoteit (PLoS ONE, 2025)
Primary production in highly stratified and oligotrophic tropical seas relies primarily on nutrient injections from a deepened mixed layer. The Red Sea, one of the warmest marine ecosystems on earth, has very few external nutrient sources. The role of mixed layer depth (MLD) on phytoplankton dynamics has predominantly been investigated in the northern part of the basin, yet a comprehensive investigation covering the entire basin is currently lacking. By integrating numerical MLD simulations and ocean colour remote sensing observations, both regionally-tuned to the Red Sea environment, the influence of vertical mixing, proxied by the MLD, on chlorophyll-a concentration (CHL) is investigated at seasonal and interannual scales. Results show that the central basin exhibits weak relationships, possibly linked to the intense mesoscale activity and the resulting horizontal advective fluxes. Remarkably, in the southern basin, even minor MLD variations (3%) seem to have a significant response in CHL (~10%). Until now, phytoplankton biomass in the south was linked to the horizontal intrusion of nutrient-rich waters from the Indian Ocean, while our results also stress the importance of vertical mixing in the redistribution of these fertile deeper layer waters to the surface lit zone. Here, we report the diverse role of deepened mixed layers in shaping CHL concentrations across various provinces in the Red Sea.